MANAJEMEN LAYANAN BIMBINGAN DAN KONSELING DI UNIVERSITAS SAPTA MANDIRI BALANGAN KALIMANTAN SELATAN - Muhammad Hafidz Ilmi; Muhammad Hiqqal; Arifin; Dian Nur Andriani (Jurnal Humaniora & Sosial Sains, 2025)
The purpose of this study was to determine how management functions—planning, organizing, mobilizing, and supervising—are implemented in guidance and counseling services at Sapta Mandiri University, Balangan, South Kalimantan. This research method is descriptive qualitative. The data used in this study are primary data sourced from informants. Secondary data, which is supporting or complementary data, was obtained from source books supporting the theoretical study in the research, journals, and through internet links, which support the study in the research. Data collection techniques were carried out through documentation and interviews with the Head of the Counseling Services Unit and Career Development Center and teaching staff at Sapta Mandiri University. Data analysis techniques include data collection, data reduction, data presentation, drawing conclusions, and verification. The results of the study indicate that the Guidance and Counseling Service Management at Sapta Mandiri University, Balangan, has implemented the POAC function in stages. Planning is systematically prepared based on the vision and mission and needs analysis. Organization has established a structure and roles, but requires complete human resources and SOPs. Mobilization has received support from the university, but is hampered by minimal training and motivation. Supervision is still in its infancy without formal instruments.